2014
DOI: 10.22452/jscp.vol5no2.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Youth’s Recreational Behaviour and its Effects on Body Mass Index (BMI)

Abstract: Youth require recreational activities to enhance their physical and mental health. This study seeks to identify the determinants of youth's recreational behaviour and effects to their body mass index by built environmental factors. A pilot study was carried out to determine the physical activity, the sedentary behaviour, accessibility and safety of recreational park, and its association with youth body weight index. Respondents comprise of 30 youth aged between 15 to 16 years, randomly selected from a few seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…For example, youths require a place to be healthy and physically active by playing sports in outdoor areas. Hence, factors such as proximity to parks from their home and the provision of sufficient and suitable facilities will affect their recreational activities (Zulkia et al, 2014). It is because it is found that youths that have convenient access to recreational facilities, which are near their homes, are more active than those without such access (Bauman et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, youths require a place to be healthy and physically active by playing sports in outdoor areas. Hence, factors such as proximity to parks from their home and the provision of sufficient and suitable facilities will affect their recreational activities (Zulkia et al, 2014). It is because it is found that youths that have convenient access to recreational facilities, which are near their homes, are more active than those without such access (Bauman et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This attitude influences the development and assessment of the availability and accessibility of recreational facilities in schools (González et al, 2014). Since physical activity among, suggested that promoting physical activities among youth also influences health, where most of the factors are modifiable factors, it is necessary to deal with these identified factors (Zulkia, Zainol, Zainol, & Nordin, 2014).…”
Section: Recreation and Policiesmentioning
confidence: 99%
“…For example, the youths are more concerned about the condition of equipment and the natural views because these criteria influence their mood and feelings to play and enjoy activities (Kahiruddin, Mohd Yunos, Mydin, & Ujang, 2015). Distance of play area with their residential areas also influence their choice to frequent a park (Danis, Sidek, & Yusof, 2014;Zulkia, Zainol, Zainol, & Nordin, 2014). Typical types of recreational park facilities, compatible with the youths comprise of baseball fields, basketball courts, picnic areas, open lawns, jogging tracks and many more.…”
Section: Literature Reviewmentioning
confidence: 99%